AKIBAT HUKUM TERHADAP PARA PIHAK DALAM PERJANJIAN APABILA TERJADI PEMBATALAN PERJANJIAN - Dewitasari, Yulia; Cakabawa Landra, Putu Tuni (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
This paper shall be titled as "The Legal Consequences of Cancellation ofAgreement towards the Parties in the Agreement". Cancellation of agreementrecognized by the Indonesian Civil Code and it has to qualify the terms of cancellations.Cancellation of the agreement, which results no agreement has ever been considered atall, brings new legal consequences for the parties in the agreement. The aims of thispaper are to understand about the cancellation terms and legal consequences thatcaused by the cancellation of the agreement. This paper applied normative analysismethod combined with statutory approach in its composition. Terms of cancellation ofthe agreement are non-fulfillment of agreement, the agreement must be a mutualagreement, and the cancellation is through the judge's decision. Agreement may becanceled if it not qualifies the terms of the agreement. Legal consequence towards theparties in the agreement is to recover just like the original state before the agreementhappened.
Keywords: legal consequences, cancellation, agreement